P187 IN SEVERE AORTIC STENOSIS, DECREASED SYSTEMIC VASCULAR RESISTANCE IS ASSOCIATED WITH A LARGER, THICKER WALLED VENTRICLE EXCEPT FOR THE SEPTUM - Anish Bhuva; Thomas Treibel; Georgia Doumou; Antonio De Marvao; Carlo Biffi; Timothy Dawes; Siana Jones; Declan O’Regan; James Moon; Alun Hughes; Charlotte Manisty (Artery Research, 2017)
Background: The ventricle in aortic stenosis (AS) is influenced by both valvular and vascular factors. The importance of afterload on left ventricular (LV) remodeling is not completely understood. Traditional imaging techniques which rely on geometric assumptions may not assess regional remodeling accurately. Aim: To understand the influence of systemic vascular resistance (SVR), systemic arterial compliance (SAC), valvulo-arterial impedance (Zva) on LV remodeling using a cardiac atlas technique. Methods: 109 patients with symptomatic severe AS awaiting surgical valve replacement (age 69±10y, 60% male, aortic valve area 0.7±0.3cm2, mean gradient 48±15 mmHg) underwent comprehensive clinical, echocardiographic and cardiovascular magnetic resonance (CMR) examinations. SVR, SAC and Zva were calculated as previously published (1). CMR LV short axis steady-state free precession cine images were segmented and co-registered using a cardiac atlas technique (2). Data were extracted and analysed using mass-univariate 3D regression modeling adjusted for age, sex, and height and accounting for multiple testing, presented as standardized ß. Results: Lower SVR correlated with increased wall thickness and larger cavity volume. SVR related changes were more prominent in the lateral wall (ß −0.3 to −0.6, p = 0.04), with no discernable influence on the septum (Figure 1). With lower SVR, LV cavity enlargement was directed away from the septum (ß −0.17 to −0.56, p = 0.002). There was no influence of SAC or Zva on 3D parameters.